Effects of a short-term resistance training protocol on risk factors for the metabolic syndrome in the elderly - Inglis, Alistair (2016)
The metabolic syndrome is strongly associated with negative health outcomes, such as type 2 diabetes, cardiovascular disease and death. The elderly are at particularly high risk of developing the metabolic syndrome, owing to the physiological and behavioural changes associated with aging. The positive influence that resistance training has on the neuromuscular system has long been evident; however, in more recent years, increasing focus has been placed on the role of RT in preventing and treating chronic disease. The majority of studies in the literature suggest that RT has a positive effect on cardiometabolic risk factors. That being said, there remain some inconsistencies. Whether improvements following RT are clinically significant and truly meaningful also remains a disputed point. Further, the physiological mechanisms underlying improvements in risk factors for the metabolic syndrome following RT have not been fully elucidated. The aim of this study was to investigate the effects of a short-term, high-repetition RT protocol with short rest periods on risk factors for the metabolic syndrome in an untrained, heterogeneous elderly population. The results suggest that RT has a positive effect on risk factors for the metabolic syndrome in the elderly. RT led to meaningful improvements in these risk factors – reducing abdominal fat and systolic blood pressure while increasing glucose tolerance. It is unclear whether RT positively affects diastolic blood pressure and the lipid profile; the present results suggest that it does not. The mechanisms underlying positive changes in cardiometabolic risk factors following RT remain complex. However, the present results highlight the role of fat and obesity in both the development and treatment/prevention of the metabolic syndrome. The majority of studies in the literature use relatively long lasting, high-frequency protocols (~48 total training sessions) to investigate the effects of RT on cardiometabolic risk factors. This study appears to be the first to show improvements in risk factors for the metabolic syndrome in the elderly following a short-term RT protocol with only 24 total training sessions. The results of the present study should be considered when prescribing exercise for the elderly. The results suggest that small doses of RT (24 hours) can have a significant, health-promoting effect. This point is important when considering that a major barrier to exercise is a lack of time.